Educational inequality and the poverty trap in teacher recruitment - Lentini Gilli, Valeria (2023)
The regional concentration of poverty and the resulting disparities in living conditions create conditions where educational inequalities are intensified. These adverse conditions could lead teachers to refuse to work in disadvantaged locations that are characterised by high incidences of poverty and low-performing students. In this paper, we estimate how poverty in the districts where the schools are situated influences the probability that teachers accept a job offer in Costa Rica. Working with data on contract offers acceptance or rejection is a methodological novelty that makes it possible to dissociate students’ poverty from the poverty of the schools’ location. The estimation of a three‐level hierarchical model allows us to deal with aggregation bias and unobserved heterogeneity. The results show evidence that district poverty is a key determinant of teachers’ rejection of offers. Although the study uses data from Costa Rica, the results indicate more generally, how educational inequity can perpetuate poverty.